Common Occupational Trauma: Is There a Relationship with Workers’ Mental Health? - Nicola Magnavita; Ilaria Capitanelli; Gabriele Arnesano; Angela Iuliano; Igor Mauro; Francesco Suraci; Francesco Chirico (Trauma Care, 2021)
Exposure to major trauma can have significant consequences for workers’ mental health, but common trauma may also result in poor mental health outcomes. This cross-sectional study retrospectively investigated the occurrence of common physical or psychological workplace trauma in 901 health, social service, and trading company workers and studied these experiences in relation to occupational stress, anxiety, and depression. Stress was measured with the effort/reward imbalance (ERI) model while anxiety and depression were evaluated with the Goldberg Anxiety and Depression Scale (GADS). Healthcare workers reported a high frequency of trauma and significantly higher levels of stress, anxiety, and depression than other workers. Even in the entire population of workers of the various professional categories, verbal violence (harassment and threats), traffic accidents, home injuries, and family bereavement were significantly associated with high levels of stress, anxiety, and depression. Major trauma survivors are known to be at increased risk of mental disorders and require support in the workplace, however, even minor repeated emotional trauma and injuries can affect mental health. During mandatory health surveillance, the occupational physician should systematically collect information on minor trauma and mental health outcomes when assessing the occupational fitness of the workers assigned to him.